Effect of Tools of Evolution Steps of Management Accounting on Operating Profit of Companies Listed in Tehran Stock Exchange - Zahra Dianati Deylami; Amir Hossein Hossein Pour; Hossein Ahmadi (مطالعات تجربی حسابداری مالی, 2015)
One important aspect of accounting research in different countries is acquiring knowledge about situation of accounting systems and finding weaknesses and gaps, providing solutions to resolve existing deficiencies, and upgrading to higher levels. According to the four steps of the evolution steps of management accounting, the higher the steps, tools of cost management becomes more advanced and reasonably the effect on operating profit more, in this study, examine effect of tools and techniques of management accounting in evolution step of management accounting form on operating profit. Statistical population of the study is financial management companies by the end of 1392 (In Solar Calendar) In Tehran Stock Exchange is accepted. Data is collected by questionnaire. The results show that if evolution step of management accounting firms goes up, operating profit will goes up too, in the meanwhile, there is a exception, that is companies are in the step two have higher operating profit than companies which are in the steps third and fourth of evolution of management accounting.